Correction: Formamidinium-based Ruddlesden–Popper perovskite films fabricated via two-step sequential deposition: quantum well formation, physical properties and film-based solar cells. Issue 5 (13th April 2022) - Lu, Jing; Yang, Tinghuan; Niu, Tianqi; Bu, Nuo; Zhang, Yalan; Wang, Shiqiang; Fang, Junjie; Chang, Xiaoming; Luo, Tao; Wen, Jialun; Yang, Yingguo; Ding, Zicheng; et al.
Abstract : Correction for 'Formamidinium-based Ruddlesden–Popper perovskite films fabricated via two-step sequential deposition: quantum well formation, physical properties and film-based solar cells' by Jing Lu et al., Energy Environ. Sci., 2022, 15, 1144–1155, DOI: ; 10.1039/D1EE02851K .